EFEKTIVITAS HUKUM PERLINDUNGAN RAHASIA DAGANG PADA NEGARA COMMON LAW, CIVIL LAW DAN ISLAMIC LAW - Nugroho, Titis Adityo (Jurnal De Lege Ferenda Trisakti, 2025)
The study entitled "The Effectiveness of Trade Secrets Law Protection in Common Law, Civil Law, and Islamic Law Countries" focuses on the legal protection of trade secrets across three different legal systems: the United States of America (Common Law), Indonesia (Civil Law), and Saudi Arabia (Islamic Law). This research utilizes qualitative methodology, analyzing and comparing the legislation and enforcement of trade secrets law in these countries. The results indicate that the effectiveness of law in protecting trade secrets is influenced by the balance between legal substance, legal structure, and legal culture. Legal substance refers to the applicable law and court decisions, legal structure focuses on law enforcement institutions, while legal culture pertains to public awareness and understanding of the law. Case studies used in this research include the case of Jack Shearer in the United States of America, Lunpia Express vs. Lunpia Delight in Indonesia, and a review of trade secrets law in Saudi Arabia. These case studies reveal that a strong law enforcement and an adequate public understanding of the law are essential in creating an effective trade secrets law system. Thefinding is relevant in the context of current digital age and globalization, where information can flow seamlessly across borders and hold significant value. An Effective legal protection of trade secrets is a key to maintaini the competitive advantage and economic value of this information.